Novel prostate brachytherapy technique: improved dosimetric and clinical outcome. - Nobes, J; Khaksar, S; Hawkins, M; Cunningham, M; Langley, SE; Laing, R (2008)
Erectile dysfunction following prostate brachytherapy is reported to be related to dose received by the penile bulb. To minimise this, whilst preserving prostate dosimetry, we have developed a technique for I-125 seed brachytherapy using both stranded seeds and loose seeds delivered with a Mick applicator, and implanted via the sagittal plane on trans-rectal ultrasound.